The prevalence of gingival enlargement among Filipinos taking nifedipine at the Philippine Heart Center - Hernandez, Errol P.; Laguna, Arvin B.; Vergel de Dios, Nannette (Adviser).
Gingival overgrowth has been reported In patients treated with Phenytoin, Cyclosporine, Na 'Valproate, Primidone, and the Barbiturates, Nifedipine, a relatively new drug which is used for the treatment of, hypertension, arrhythmia, and angina, pectoris, has also beens reported to induce the same gingival overgrowth as that of phenytoin. In the Philippines, no studies have ever been reported regarding the occurence of Nifedipine-induced gingival, overgrowth. This is a descriptive study on the prevalence of gingival enlargement among Filipinos taking Nifedipine at the Philippine Heart center. Thirty-six patients taking Nifedipine regularly for at least 9 most tins were clinically examined. Ten out of the 36 subjects were positive on gingival enlargement. We conclude that gingival, enlargement does occur in Filipino patients taking Nifedipine at the Philippine Heart Center with a prevalence of 27.77%.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gingival hyperplasia; Nifedipine